Family, friends and personal communities: Changing models-in-the-mind - Ray Pahl; Liz Spencer (University of Essex, Institute for Social and Economic Research (ISER), 2010)
Models-in-the-minds about the proper and right way to be a true friend or to do family behaviour may not necessarily fit lived experience, especially in cases where relationships become fused and distinctions between family and friend become blurred.. We suggest the idea of a personal community the micro-social world of significant others for any given individual as a practical schema for capturing the set of relationships in which people are actually embedded.
Keywords: 330; Familiensoziologie; Soziale Beziehungen; Gemeinschaft; Verhaltensökonomik; Theorie